The kinetics oxidative degradation of chitosan in formic acid with the presence of hydrogen peroxide. (November 2019) - Purwanto, E; Connor, J; Ngothai, Y
Abstract: The chitosan degradation in formic acid solution with the presence of hydrogen peroxide was investigated in this work. Temperature and reaction time had a significant effect on reducing the molecular weight of chitosan, and it is clear that it decreased the molecular weight faster at the first 15 minutes of reaction time. Therefore, the molar concentration of chitosan in the solution increased with temperature and reaction time. The reaction order was determined from the molar changes of chitosan on reaction time and found followed -0.1 reaction order to the molar concentration of chitosan. The Arrhenius equation was used to study the correspondence influence of reaction temperature on the degradation reaction rate constant. The results suggest that the values of degradation rate constant increased with higher reaction temperature. The value of activation energy was determined under the experimental operating conditions examined to be 99.8 kJ/mol. The FT-IR spectra demonstrated that there was no change in the chemical structure of chitosan before and after the degradation reaction.